Is the Developing World Catching up? Global Convergence and National Rising Dispersion - Bussolo, Maurizio; De Hoyos, Rafael E.; Medvedev, Denis (Washington, DC: World Bank, 2012)
The present study uses the GIDD, a CGE-microsimulation model for Global Income Distribution Dynamics, to understand the ex-ante dynamics of global income distribution. Three main robust results emerge. First, under a set of realistic assumptions, there will be a reduction in global income inequality by 2030. This potential reduction can be fully accounted for by the projected convergence in average incomes across countries, with poor and populous countries growing faster than the rest of the world. Second, this convergence process will be accompanied by a widening of income distribution in two-thirds of the developing countries; the main cause being increasing skill premia. Third, a trend that may counter-balance the potential anti-globalization sentiment is the emergence of a global middle class: a group of consumers who demand access to, and have the means to purchase, international goods and services. The results show that the share of these consumers in the global population is likely to more than double in the next 20 years. These ex-ante trends in global income distribution suggest that the mid-1990s could be seen as a turning point after which global inequality began showing a negative tendency.